Linguistic skills required by Portuguese employers in the past 40 years: the case of office management professionals: el caso de los profesionales de secretariado - Simões, Anabela Valente; Calvão, Ana Rita; Simões, Anabela Valente (Millenium - Journal of Education, Technologies, and Health, 2019)
Introduction: With internationalization and globalization, language skills are increasingly useful in today’s labour market, especially in functions that require contacts with other markets, such as secretarial/management support positions. Objectives: Identify and analyse the language skills required in job advertisements for secretarial /office management professionals. Methods: Study of 844 job ads for secretarial/office management positions, published in the newspaper Jornal Expresso (1978-2018), in March. Possible requirements for language skills used in each advertisement were examined. The data was studied globally and in terms of temporal evolution. Results: 78.8% of the analysed advertisements have language requirements, predominating those in which 2 languages are requested. The most requested foreign languages are English and French. In 67.2% of the references, there is an explicit mention of oral or written competencies. There is a great diversity of formulations referring to the level of proficiency sought, prevailing the requests for “domain” in the cases of English, French and German, and “satisfactory knowledge/knowledge” for Spanish. Conclusion: Language skills are essential for secretarial/office management professionals. They must have a good knowledge of their mother tongue, as well as of at least two foreign languages in which they must demonstrate good levels of proficiency.